Human Pathogenic Microorganisms in Fresh Produce Production: Lessons Learned When Plant Science Meets Food Safety - Xingchen Zhao; Leo Van Overbeek; Catherine M. Burgess; Nicola Holden; Fiona Brennan; Gro S. Johannessen; Ana Allende; Monica Höfte; Bart Cottyn; Joël F. Pothier; Adam Schikora; Mieke Uyttendaele (Journal of Food Protection)
To enhance control of human pathogenic microorganisms in plant production systems, an EU COST Action (HUPLANTcontrol CA16110) was initiated, bringing together microbiologists in food, environmental, and plant microbial ecology. This article summarizes the outcomes of multiple workshops and the four main lessons learned: (i) many terminologies need further explanation to facilitate multidisciplinary communication on the behavior of human pathogens from preharvest plant production to postharvest food storage, (ii) the complexity of bacterial taxonomy pushes microbial hazard identification for greater resolution of characterization (to subspecies, or even strain level) needing a multimethod approach, (iii) hazard characterization should consider a range of factors to evaluate the weight of evidence for adverse health effects in humans, including strain pathogenicity, host susceptibility, and the impact of the plant, food, or human gut microbiome, (iv) a wide diversity of microorganisms in varying numbers and behaviors coexist in the plant microbiome, including good (beneficial for plant or human health), bad (established human or plant pathogens), or ugly (causing spoilage or opportunistic disease). In conclusion, active listening in communication and a multiperspective approach are the foundation for every successful conversation when plant science meets food safety.